(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
: It is well known that children’s bodies are in a stage of active development, making them more susceptible to various injuries. These injuries can negatively impact their physical and mental health, academic performance, and social activities, ultimately limiting their future opportunities. Additionally, they increase financial burdens on both the healthcare system and families. Therefore, studying the prevalence of domestic injuries among school-aged children and addressing this issue as a socially significant concern is of great importance